The Influence of School Leadership, Teacher Competence, and Work Discipline on Teacher Performance at SMA Walisongo Semarang - Sri Murtini (Innovative Pedagogy and Education Studies, 2024)
This study aims to examine the influence of school leadership, teacher competence, and work discipline on teacher performance at SMA Walisongo Semarang. A quantitative research approach with a correlational design was employed in this study. The population consisted of all teachers at SMA Walisongo Semarang, with the sample determined using a total sampling technique. Data were collected through structured questionnaires using a Likert scale to measure school leadership, teacher competence, work discipline, and teacher performance. Prior to hypothesis testing, the data were analyzed using validity, reliability, and classical assumption tests. Multiple linear regression analysis was applied to examine both partial and simultaneous effects of the independent variables on teacher performance. The results indicate that school leadership, teacher competence, and work discipline each have a significant positive effect on teacher performance. Furthermore, the simultaneous test shows that these three variables collectively contribute significantly to improving teacher performance. These findings highlight the importance of effective school leadership, continuous development of teacher competence, and the enforcement of work discipline to enhance teacher performance and overall educational quality.